La Universitat de València en el segle XVI. Orígens, transformacions i consolidació. - FELIPO ORTS, AMPARO (Scripta, 2020)
The founding of the University of Valencia was the culmination of a long history that dates back to King James I's aim to give university status to the schools created after the conquest. Its consolidation drawn up by municipal magistrates in 1499, the papal bull in 1500 and the royal privilege in 1502 led to its official inauguration under the municipal board. From then on, the increase in the university's budget and the city's struggle to finance it called for new solutions, which culminated with the bull issued by Sixtus V for the creation of the pavordía chairs (title granted by the church) in 1585. Thus, the City Council and the Church proceeded to jointly sustain the university, which was also contributed to by the Crown mainly in the form of visits. In this context, the Constitutions of 1611 formed an instrument to consolidate the transformations carried out in the centre since its creation.